Study protocol of a breathing and relaxation intervention included in antenatal education: a randomised controlled trial (BreLax study) - Daly, Deirdre (My University, 2024)
Background: Antenatal education is part of antenatal care in many countries. Physical and mental preparation for childbirth and information on pain management are considered key elements of antenatal education classes. Evidence suggests that women who participate in antenatal education classes appear to benefit in terms of self-efficacy and childbirth experience. In particular, women with increased fear of childbirth benefit from trained breathing and relaxation techniques in antenatal education. However, little is known about the effect of breathing and relaxation techniques on the outcomes of healthy pregnant women without fear of child-birth or who do not have medical or obstetric risks, or on neonatal outcomes. Objective: The aim of this study is to test whether including a breathing and relaxation technique in an antenatal education class will improve self-efficacy towards birth compared to a standard antenatal education class. Methods: The study will be a two-armed randomised controlled trial (RCT). Healthy pregnant women between the 12th and 30th week of gestation with singleton low-risk pregnancies and who are receiving routine antenatal care will be recruited in a hospital in Switzerland. All women included will attend an 8-hour antenatal education class. The intervention group will additionally practise a breathing and relaxation technique, receive a handbook to guide their exercise practice at home, and be provided with access to an online brochure with video and audio recordings for guidance. Data on maternal and neonatal outcomes will be collected after recruitment, in the 37th week of pregnancy, and two to four weeks postpartum. Discussion: The effectiveness of including a breathing and relaxation technique in antenatal education classes on women’s self-efficacy is discussed as a means to improving women’s pregnancy and childbirth outcomes.
PUBLISHED
Keywords: Breathing exercises; Labour and birth; PROTOCOL; RELAXATION; Randomised trial